PENGARUH EFEKTIVITAS IKLAN YOUTUBE TERHADAP BRAND IMAGE - Helena, Monique; Natalia, El Chris (Tuturlogi: Journal of Southeast Asian Communication, 2021)
ABSTRACTAdvertising is used by companies as a way to market products and services. YouTube is currently the most popular social media in Indonesia and has become a platform of marketing the company's products and services. Head & Shoulders, which is under the auspices of the Procter & Gamble company uses YouTube in marketing and promoting its products. This research focuses on Joe Taslim's “Head & Shoulders” Bloopers YouTube ad. This study aims to determine the influence of the effectiveness of Joe Taslim's "Head & Shoulders" YouTube Bloopers ad on the formation of the company's brand image. The variable in this study is the effectiveness of advertising with dimensions, namely awareness, knowledge, likes, and choices. The brand image variable uses the dimensions of brand identity, brand personality, brand association, brand behavior and attitudes, as well as brand competence and benefits. This research uses an explanative quantitative method. The data was collected through survey methods and online questionnaires to 100 respondents. The result of the analysis indicates that there is a positive influence between Joe Taslim's “Head & Shoulders” YouTube Bloopers ad on the formation of the company's brand image. Keywords: marketing communication, effectiveness of ads, brand image  ABSTRAKIklan digunakan perusahaan sebagai suatu cara untuk memasarkan produk dan jasa. YouTube saat ini merupakan media sosial paling populer di Indonesia dan telah menjadi sarana untuk memasarkan produk dan jasa dari perusahaan. Head & Shoulders, yang berada di bawah naungan perusahaan Procter & Gamble menggunakan YouTube dalam memasarkan dan mempromosikan produknya. Penelitian ini berfokus pada iklan YouTube Bloopers Joe Taslim “Head & Shoulders”. Penelitian ini bertujuan untuk mengetahui pengaruh efektivitas iklan YouTube Bloopers Joe Taslim “Head & Shoulders” terhadap pembentukan brand image perusahaan. Variabel pada penelitian ini adalah efektivitas iklan dengan dimensi, yaitu kesadaran, pengetahuan, menyukai, dan pilihan. Pada variabel brand image menggunakan dimensi identitas merek, kepribadian merek, asosiasi merek, perilaku dan sikap merek, serta kompetensi dan manfaat merek. Penelitian ini menggunakan metode kuantitatif eksplanatif. Pengumpulan data dilakukan melalui metode survei dan penyebaran kuesioner secara daring kepada 100 responden. Hasil analisis menunjukkan terdapat pengaruh positif antara iklan YouTube Bloopers Joe Taslim “Head & Shoulders” terhadap pembentukan brand image perusahaan. Kata Kunci: komunikasi pemasaran, efektivitas iklan; citra merek